PENINGKATAN KEMAMPUAN MANAJERIAL KEPALA LEMBAGA PAUD DI KECAMATAN NUSA PENIDA - Mutiara Magta; Dewa Ayu Puteri Handayani (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2019)
Every year the average number of PAUD institutions in Bali increases by one hundreds. This increase in quantity should be directly proportional to the improvement in quality. However, based on the evaluation results of the BAN PAUD PNF accreditation agency in Bali Province, in standard 6 regarding the management of institutions it often has the lowest value than other standards so that development activities are needed for the managerial / managerial skills of PAUD institutions. Based on the results of interviews with several heads of PAUD institutions in Nusa Penida Subdistrict, it is known that in this sub-district managerial training has never been held. Then the purpose of implementing community service is to improve the managerial ability of the head of PAUD in managing PAUD institutions in Nusa Penida sub-district through training and mentoring. This activity was attended by 22 heads of PAUD institutions with a pattern of seminars and training and mentoring for three days. This activity produced program development documents and PAUD agency program report documents and significantly increased the knowledge of activity participants towards the management of the institution.